Konsep Wahyu dan Kenabian serta Implikasinya terhadap Pandangan Dunia Islam - Syafii, M.; Sudiarto, Sudiarto; Shidiq, M.; Sumiran, Sumiran (TSAQOFAH, 2026)
Revelation and prophethood are two fundamental concepts in Islam that serve as the main pillars in shaping the Islamic worldview, functioning not only as theological foundations but also as epistemological, ontological, axiological, and anthropological points of reference that structure how Muslims understand reality, knowledge, values, and life’s ultimate purpose. This article aims to examine the concepts of revelation and prophethood from an Islamic perspective and to explain their implications for the formation of the Islamic worldview amid the challenges of modern thought. The study employs a qualitative approach with a library research design, using conceptual, thematic, and critical-synthetic analysis of primary sources in the form of the Al-Qur’an and Sunnah, as well as secondary sources including classical and contemporary scholarly works and relevant journal articles. The findings show that revelation is understood as a transcendent source of knowledge that is absolute and authoritative, while prophethood functions as the channel for conveying revelation in an authentic and final manner. Epistemologically, revelation serves as the standard of truth for reason and empirical experience; ontologically, it shapes a view of reality that encompasses both physical and metaphysical dimensions; axiologically, revelation and prophethood establish universal and immutable moral and value standards; and anthropologically, they provide direction for human life as servants and vicegerents (khalifah) on earth. This article affirms that the concepts of revelation and prophethood remain relevant as foundational bases for shaping an integral Islamic worldview that offers constructive answers to crises of meaning, value relativism, and secularization in the modern era.